Effect of NPK Fertilizers on the Performance of Cassava Varieties (Manihot esculenta Crantz) in Humid Tropics, Niger Delta, Nigeria - Lawson T. S. (Current Research Progress in Agricultural Sciences Vol. 10, 2025)
Primary macronutrients play a very important role in improving the yield and quality of crops. Three main elements are nitrogen, phosphorus, and potassium (N, P, and K) and are required in abundance. They must be readily available through soil medium or fertilizer. An experiment was conducted to determine the performance of three cassava varieties with two NPK fertilizer types. The study was done at the Rivers State University Teaching and Research Farm in Port Harcourt, between March 2021 and February 2022. The treatments were cassava varieties TMS 95/0289, TMS 96/0523, and TME 419. NPK fertilizers were NPK 15-15-15 and NPK 20-10-10. The treatments were combined in a split-plot arrangement in a Randomized Complete Block Design (RCBD) replicated three times. Parameters evaluated were the number of branches per stand and canopy width which were assessed from 10 weeks after planting and subsequently at 4 weekly intervals. Fresh/dry pulp weight and fresh/dry peel weight were determined after crop harvest. The evaluation of the performance of three cassava varieties was studied using two compound fertilizer types at the Teaching and Research Farm, Rivers State University Port Harcourt between March 2021 and February 2022. The treatments were combined in a split-plot arrangement in a Randomized Complete Block Design (RCBD) with three replicates. Parameters evaluated were the number of branches and canopy diameter at four weekly intervals starting from the tenth week after planting and ending with fresh/dry pulp weight and fresh/dry peel weight were also taken. Results show that cassava variety TMS 95/0289 interacting with NPK 15-15-15 produced the highest branches per plot (24.7), TMS 96/0523 interacting with NPK 15-15-15 produced the widest canopy diameter per stand (263.1cm), fresh peels weight and dry peels weight (129.7g and 100.3g). TME 419 interacting with NPK 15-15-15 compound fertilizer produced the highest fresh and dry pulp weight with mean values of 722.7 and 487.0. Application of NPK fertilizer especially NPK 15-15-15 enhanced the number of branches, dry pulp weight, dry peel weight and canopy diameter. TME 419 had higher fresh/dry pulps and dry peels weight while TMS 96/0523 had high fresh peels weight and canopy width respectively. Whereas cassava variety TMS 95/0289 was high in the number of branches. Thus it is recommended that TME 419 be introduced to farmers as it produces the highest pulp weight per stand. Also, fertilizer NPK 15-15-15 is a preferred NPK fertilizer as it has the capability to increase the number of branches, canopy width, peel weight and pulp weight in comparison with NPK 20-10-10. Further growth and yield were mostly enhanced with NPK 15-15-15 fertilizer application compared to NPK 20-10-10. However, more field research on these fertilizers is needed to better understand their effects on cassava performance.